2020
DOI: 10.1210/clinem/dgaa029
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the Hemoglobin Glycation Index on the Diagnosis of Prediabetes and Diabetes

Abstract: Objective Fasting plasma glucose (FPG), 2-hour plasma glucose (2hPG) from a 75-g oral glucose tolerance test (OGTT) and glycated hemoglobin (HbA1c) can lead to different results when diagnosing prediabetes and diabetes. The Hemoglobin Glycation Index (HGI) quantifies the interindividual variation in glycation resulting in discrepancies between FPG and HbA1c. We used data from the Vitamin D and Type 2 Diabetes (D2d) study to calculate HGI, to identify HGI-associated variables, and to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 41 publications
4
27
3
Order By: Relevance
“…Although population variation in postprandial glucose undoubtedly contributes to population variation in HbA1c and HGI, there were no biologically significant positive or negative trends in 2‐h OGTT glucose levels in low‐, moderate‐ or high‐HGI diabetes treatment–naïve adult participants as a whole (Table 3 ) or when subdivided into normal, prediabetic and diabetic subgroups by OGTTs (Table 4 ). Lack of association between the HGI and 2‐h OGTT in the present study and in three previous studies 2 , 15 , 32 strongly suggests that population variation in the HGI based on FPG is not an artefact of person‐to‐person variation in postprandial blood glucose concentration.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Although population variation in postprandial glucose undoubtedly contributes to population variation in HbA1c and HGI, there were no biologically significant positive or negative trends in 2‐h OGTT glucose levels in low‐, moderate‐ or high‐HGI diabetes treatment–naïve adult participants as a whole (Table 3 ) or when subdivided into normal, prediabetic and diabetic subgroups by OGTTs (Table 4 ). Lack of association between the HGI and 2‐h OGTT in the present study and in three previous studies 2 , 15 , 32 strongly suggests that population variation in the HGI based on FPG is not an artefact of person‐to‐person variation in postprandial blood glucose concentration.…”
Section: Discussioncontrasting
confidence: 55%
“…The suitability of the diabetes treatment-naïve adult NHANES participants as the reference population and model for HGI in demographically diverse human populations is supported by the fact that our results confirm what has been consistently reported in the literature, including observations of (1) disproportionately more black participants having a higher HGI independent of diabetes classification; (2) biologically relevant trends between a higher HGI and older age, higher BMI and higher CRP in normal and prediabetic participants, but not in diabetic participants; and (3) lack of association between HGI and 2-h OGTT results, except possibly in individuals with new-onset diabetes. The association between a higher HGI and female sex observed in the present study has been reported in some studies 3,6,8,11,32 but not consistently across studies.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…5 It is striking that associations with higher HbA1c, in relation to metrics of glucose exposure, and age are not consistent between studies with disparate clinical and demographic characteristics. Women were over-represented in the highest hemoglobin glycation index (HGI) groups in one study of individuals without diabetes 7 and in a post-hoc analysis of the ACCORD trial in type 2 diabetes, 6 but the opposite was true in another cohort of individuals without diabetes. 8 Similarly, higher HGI was associated with older age in one study (no diabetes) 8 and younger age in the ACCORD study (type 2 diabetes), 6 but no significant age relationship was observed in another (no diabetes).…”
Section: Discussionmentioning
confidence: 99%
“…4 Age, gender, and race have also been identified as factors that can affect the association between glucose exposure and HbA1c. [5][6][7][8] Significant discrepancy between HbA1c and average glucose exposure has the potential to affect individuals who may be exposed to inappropriate intensification of glucose-lowering therapy or inappropriate therapeutic inaction. 2,6 With increasing use of interstitial glucose monitoring systems, greater attention is being paid to metrics such as "time in range" and average glucose 3 in recognition of the potential limitations of HbA1c.…”
Section: Introductionmentioning
confidence: 99%